2023
DOI: 10.1038/s41598-023-28587-z
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic and oleophobic microtextured aluminum surface with long durability under corrosive environment

Abstract: Superhydrophobic (SHP) and oleophobic aluminum surfaces have been prepared through the combination of a scalable chemical microtexturing process and surface functionalization with long-chained polyfluoroalkyl moieties. The effect of an anodic layer on the microtextured surface has been assessed considering surface morphology, superhydrophobicity, surface mechanical properties and corrosion protection enhancement. The surface functionalization with polyfluoroalkyl moieties has been tackled in two different ways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Hou et al [3] demonstrated that anticorrosive coatings constitute the largest proportion (66.15%) of direct corrosion costs. Currently, the anticorrosive coatings in use include (1) graphene coatings [4][5][6] are primarily used on metal substrates in marine environments or those exposed to high concentrations of chloride ions [7,8]; (2) epoxy coatings [9][10][11] are mainly applied to metal substrates in industrial warehouses with lower protection needs [12]; (3) polyurethane coatings [13][14][15], due to their excellent stress-strain properties, are preferred for metal substrates in scratchprone environments [16,17]; (4) ceramic coatings [18][19][20], known for their high-temperature resistance, are primarily used on aerospace component surfaces [21,22]; and (5) superamphiphobic coatings [23,24], which act as active protective layers on substrates and can function in a variety of complex environments [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Hou et al [3] demonstrated that anticorrosive coatings constitute the largest proportion (66.15%) of direct corrosion costs. Currently, the anticorrosive coatings in use include (1) graphene coatings [4][5][6] are primarily used on metal substrates in marine environments or those exposed to high concentrations of chloride ions [7,8]; (2) epoxy coatings [9][10][11] are mainly applied to metal substrates in industrial warehouses with lower protection needs [12]; (3) polyurethane coatings [13][14][15], due to their excellent stress-strain properties, are preferred for metal substrates in scratchprone environments [16,17]; (4) ceramic coatings [18][19][20], known for their high-temperature resistance, are primarily used on aerospace component surfaces [21,22]; and (5) superamphiphobic coatings [23,24], which act as active protective layers on substrates and can function in a variety of complex environments [25][26][27].…”
Section: Introductionmentioning
confidence: 99%